To the 90-th Anniversary of Dmitrii Vasil’evich Volkov’s Birthday - Shul’ga, N. F.; Bakai, A. S.; Peletminskii, S. V.; Slyusarenko, Yu. V.; Zheltukhin, A. A.; Uvarov, D. V. (Ukrainian Journal of Physics, 2019)
-